Analysis on traffic dynamics of signalized two-lane four segment intersection using agent-based modeling - Amoranto, Paolo S.; Chavez, Joe-Mar O.; Tomacruz, Arvin John C.
Vehicular traffic is one problem encountered by different countries worldwide. Over the years, different studies have been conducted about traffic in order to better analyze the dynamics and mechanics behind it. This study on vehicular traffic in particular is focused on the dynamics behind signalized two-lane four-segment intersection. Its goal is to be able to determine how the dynamics work and to be able to provide a better configuration for the traffic schemes around aforementioned intersections. Four experiments are conducted in this study in order to get sufficient data for analyses. The results of the experiments will then be utilized to generate a conclusion as well as possible recommendations for future studies.